Biological Treatments For Pustular Psoriasis: A Systematic Review (Journal of Pharmaceutical Negative Results, 2019)
Objectives: To gather and analyze recent research on biologic treatments for pustular psoriasis, focusing on their effectiveness and safety. Methods: A thorough search across four databases identified 400 relevant publications. After removing duplicates using Rayyan QCRI and screening for relevance, the search yielded 614 publications, of which 92 full-text articles were reviewed, and 6 met the eligibility criteria for evidence synthesis. Results: We included six studies with a total of 208 GPP patients and less than half of them were females 58 (27.9%). In this review, biological treatments for pustular psoriasis, including secukinumab, ixekizumab, adalimumab, brodalumab, and guselkumab, were evaluated for efficacy and safety. Secukinumab showed consistent clinical improvement with manageable side effects like nasopharyngitis and pruritus. Ixekizumab demonstrated substantial efficacy, with mild adverse events, primarily injection site reactions. Adalimumab was effective even in resistant cases, though 30% of patients experienced significant adverse events, including hypocalcemia. Brodalumab rapidly alleviated symptoms, with nasopharyngitis being the most common side effect. Guselkumab showed therapeutic value with manageable side effects such as diarrhea and arthralgia. Overall, all treatments were effective, with tolerable safety profiles, though larger, more diverse studies are needed. Conclusion: Biologic treatments like secukinumab, ixekizumab, adalimumab, brodalumab, and guselkumab are emerging as reliable and effective options for treating Generalized Pustular Psoriasis. They offer better outcomes and longer-lasting effects compared to non-biologic therapies, making them a valuable addition to the treatment toolkit for GPP. However, more research is needed to fully understand the long-term safety of these treatments. Going forward, studies should aim to address the current gaps and further explore the potential of biologics to provide lasting relief for patients living with this challenging skin condition.